Sensitivity of Cumulus Physics in ARW Model on Track of Tropical Cyclones ‘Amphan’ and ‘Bulbul’ over the Bay of Bengal - Ali, Md Idris; Alam, Md Mahbub (Journal of Engineering Science, 2024)
The Advanced Research Weather Research and Forecasting (ARW) model performance can be improved by analyzing the sensitivity of the physical parameterization schemes. In order to revalidate the performance of the ARW model in relation to the selection of Cumulus Physics (CP) schemes, the sensitivity of CP schemes for Tropical Cyclones (TCs) over the Bay of Bengal (BoB) region has been examined. National Centre for Environment Prediction (NCEP)’s Final Reanalysis (FNL) data (1010) have been used as lateral and initial conditions in the ARW model. The model has been configured in a single domain and runs for four different initial conditions in simulating TC ‘Amphan’ and for three different initial conditions in simulating TC ‘Bulbul’. In this study, average track errors have been found between 40-50 km for Kain-Fritsch Cumulus Potential (KFCP) and Multi-Scale Kain-Fritsch (MSKF) schemes for TC Amphan and below 60 km for the Kain Fritsch (KF) scheme for TC Bulbul. Lower landfall position error has been found below 60 km for the KF scheme for TC Amphan, and 40 km for KFCP and MSKF schemes for TC Bulbul. Journal of Engineering Science 15(1), 2024, 119-129